INTERNATIONAL COOPERATION IN THE INVESTIGATION OF BRIBERY CASES AT PT. GARUDA INDONESIA - Fiki N. Ardiansyah,; Eva Achjani Zulfa,; Zulkarnein Koto, (International Journal of Innovative Technologies in Social Science, 2022)
Bribery case at PT. Garuda Indonesia is a cross-jurisdictional corruption case involving several countries. The purpose of this research is to analyze the international cooperation carried out by the Corruption Eradication Commission (KPK) in the investigation of bribery cases at PT. Garuda Indonesia. The research method used is a qualitative approach with a case study method. The data analysis used is the theory of international cooperation in dealing with corruption, jurisdictional theory, and the concept of transnational crime. The results of his research show that the bribery case at PT. Garuda involves multiple jurisdictions, namely: Indonesia, United Kingdom, Singapore, Hong Kong, France, and Canada. KPK-SFO-CPIB international cooperation process shows a new format of cooperation because it is carried out by the anti-corruption agency with a parallel investigations format. KPK cooperates with the agency through the MoU and MLA mechanisms referring to international instruments, namely the United Nations Convention Against Corruption (UNCAC). Even though the platform has been created, there are still many challenges and obstacles due to differences in the legal system, language and time. KPK encountered problems when it wanted to cooperate with Hong Kong's ICAC, Canada's RCMP, and France's PNF. The keys to the success of KPK in this collaboration are the diplomatic approach, speed of coordination, accuracy in strategies of communication, and commitment, as well as trust and adjustment of cooperation mechanisms according to the standards of each country.